Alumina Polished Glassy Carbon Electrode as a Simple Electrode for Lower Potential Electrochemical Detection of Dopamine in its Sub‐micromolar Level. Issue 3 (3rd September 2015) - Thirumalraj, Balamurugan; Palanisamy, Selvakumar; Chen, Shen‐Ming; Sayee Kannan, R.
Abstract: The electrochemical behaviour of dopamine (DA) at a cleaned and alumina polished glassy carbon electrode (GCE) was studied using cyclic voltammetry (CV). The CV studies revealed that alumina polished GCE (AGCE) shows an enhanced oxidation peak current response with 217 mV negative potential shift towards DA than that of cleaned GCE. The differential pulse voltammetry result shows that the AGCE detects the DA in the linear concentration ranges from 0.15 to 25.25 µmol L −1 . The limit of detection was calculated as 0.046 µmol L −1 with a sensitivity of 3.74 µA µmol L −1  cm −2 for the determination of DA. The fabricated AGCE shows a satisfactory selectivity, practicality along with appreciable repeatability and reproducibility. Abstract :